2020
DOI: 10.1128/aem.00526-20
|View full text |Cite
|
Sign up to set email alerts
|

F-Specific RNA Bacteriophages Model the Behavior of Human Noroviruses during Purification of Oysters: the Main Mechanism Is Probably Inactivation Rather than Release

Abstract: Noroviruses (NoV) are responsible for many shellfish outbreaks. Purification processes may be applied to oysters before marketing to decrease potential fecal pollution. This step is rapidly highly effective in reducing Escherichia coli; nevertheless, the elimination of virus genomes has been described to be much slower. It is therefore important to identify (i) the purification conditions that optimize virus removal and (ii) the mechanism involved. To this end, the effects of oyster stress, nutrients, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(84 reference statements)
2
5
0
Order By: Relevance
“…Infectious FRNAPHs appeared to be inactivated faster in water than in the mussels, which highlighted the protective effect of the mussel tissue. T90 values of~20 days are currently described in the literature for the reduction of infectious FRNAPHs in oysters at 10 • C [25,36], which is in the same range as our study.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Infectious FRNAPHs appeared to be inactivated faster in water than in the mussels, which highlighted the protective effect of the mussel tissue. T90 values of~20 days are currently described in the literature for the reduction of infectious FRNAPHs in oysters at 10 • C [25,36], which is in the same range as our study.…”
Section: Resultssupporting
confidence: 85%
“…These specific interactions favor HuNoV accumulation in digestive tissues [38,40]. The accumulation of FRNAPHs in the digestive tissue of oysters is also well documented [25,36,41]. Further experiments are required to better understand the specific and/or non-specific interactions between infectious FRNAPHs and the soft tissue of zebra mussels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, all oysters in the tested population were found to be contaminated when the mean concentration tested above 300 gcg −1 (Hunt 2019 ). Additionally, two recent studies investigated the FRNA bacteriophage type II (norovirus surrogate) removal from oysters during depuration using genomic and infectivity methods (Leduc et al 2020 ; Younger et al 2020 ). These studies indicated that viruses may either be inactivated in oysters during depuration (Leduc et al 2020 ) or, as suggested by Younger et al ( 2020 ), destroyed and removed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two recent studies investigated the FRNA bacteriophage type II (norovirus surrogate) removal from oysters during depuration using genomic and infectivity methods (Leduc et al 2020 ; Younger et al 2020 ). These studies indicated that viruses may either be inactivated in oysters during depuration (Leduc et al 2020 ) or, as suggested by Younger et al ( 2020 ), destroyed and removed. Despite the differences in the concluded viral reduction mechanisms these findings could indicate that the virus genome copies detected using RT-PCR methods are, at least in part, only footprints left by the infectious virus particles and they no longer have the capability of causing infection especially at low concentrations (i.e.…”
Section: Discussionmentioning
confidence: 99%